KEDUDUKAN HADIST DALAM PEMBENTUKAN HUKUM - Abdul Wahab Syakhrani; Hidayah (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
All Muslims, both naql experts and aql experts, have agreed that hadith/sunnah is the basis of Islamic law, namely one of the sources of Islamic law and also agree on the obligation to follow hadith as required to follow the Al-Qur`an. Many verses of the Qur'an and Al- Hadith explain that hadith is a source of Islamic law besides the Al-Qur'an which must be followed as follows the Al-Qur'an, both in the form ofawamir and nawahnya.